Português língua estrangeira : como aprendem estudantes secundaristas em intercâmbio no Brasil ? - Martins, Paula Garcia Solano (2008)
In this study we will focus on the acquisition of Portuguese as a Foreign Language by secondary students during their exchange experience in Brazil. Based on the information given by them in questionnaires and on the texts in Portuguese written in the last month of their stay in Brazil, we will assess the impact of two original pedagogical instruments (Language Camp and Português por Carta) created by the exchange organization Youth For Understanding on the communicative competence of their students. In order to do so, we will compare the written production of three different student groups, divided according to the exchange organization they belong to and to the type of formal aid they had while learning Portuguese. Our analysis of the communicative competence of these students will be conducted in two levels: a) the sentence level, in which we will examine the cases of inappropriateness and error in the use of the language code; b) the textual level, in which we will consider the appropriateness of the texts in relation to the tasks proposed, as well as the cohesion and coherence of the texts.